2008
DOI: 10.1007/s00508-008-0985-6
|View full text |Cite
|
Sign up to set email alerts
|

Not carried away by a moonlight shadow: no evidence for associations between suicide occurrence and lunar phase among more than 65,000 suicide cases in Austria, 1970–2006

Abstract: This large-sample evidence strongly suggests no lunar effects on the timing of completed suicide. Scattered previous evidence in support of such effects in all likelihood was spurious; that is, was due to statistical type 1 errors or erroneously taking calendrical periodicities of suicide occurrence that are real as evidence for lunar effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
2
6
1
1
Order By: Relevance
“…This research proposes an empirical model of the relation� ship between suicide attempts and other health�risk and problem behaviors. Our study confirms specific lit� erature findings [7,22,23] that teenage suicidal behav� iors are influenced by a broad range of factors. Accord� ing to the univariate analysis, many adolescents report� ed one or more risk or problem behaviors.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This research proposes an empirical model of the relation� ship between suicide attempts and other health�risk and problem behaviors. Our study confirms specific lit� erature findings [7,22,23] that teenage suicidal behav� iors are influenced by a broad range of factors. Accord� ing to the univariate analysis, many adolescents report� ed one or more risk or problem behaviors.…”
Section: Discussionsupporting
confidence: 78%
“…Although suicidal behaviors are clearly complex and multifactorial [7], some risk factors tend to serve as common denominators in a large pro� portion of cases, one of them being substance use and abuse. A large number of studies have demonstrated that suicide attempts are more likely to occur among adolescents who drink frequently or heavily and among adolescents who use illicit drugs [3,4,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Another large-scale study was conducted by Voracek et al in Austria. They evaluated 65,206 suicide attempts between 1970 and 2006 and found no relationship between lunar phases and suicide attempts [19]. In the present study, we also did not find any significant relationship between suicide attempts and lunar phases.…”
Section: Discussioncontrasting
confidence: 66%
“…Unfortunately for this theory, higher tides do not occur only during the full moon but approximately twice a month, around the new moon and the full moon due to the alignment of the sun, moon, and earth. 33 There was no increase in suicides 34,35 or traumas during the full moon. 29 Ultimately, could the full moon, whether through sleep deprivation or other mechanism, create a significant change in human behavior?…”
Section: Discussionmentioning
confidence: 90%